2018
DOI: 10.1007/s00394-018-1780-4
|View full text |Cite
|
Sign up to set email alerts
|

Acute and residual effects of aerobic exercise on fructose-induced postprandial lipemia on lean male subjects

Abstract: Fructose consumption (0.5 g/kg) severely increased postprandial TG on day 1, but not on day 2. Previous exercise performance could lead to ~ 30% reduction on the AUC of postprandial TG in 13 h, but not after 37 h followed by fructose consumption. The regularity of physical exercise practice seems to be essential to promote a constant hypolipemic effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 71 publications
0
5
0
1
Order By: Relevance
“…Since 2014, 36 studies have confirmed that exercise performed on the evening prior to a morning high-fat meal (that is, a meal containing above 0.7 g of fat per kg body mass) lowers PPL, compared to no exercise. This has been shown in young, middle-aged and/or older men [14,21,[33][34][35][36][37][38][39][40][41][42]22,43,76,77,23,[27][28][29][30][31][32], young men and women [44], young or middle-aged women [45,67], normal and overweight individuals [68], overweight and obese individuals [24,46,47] and adolescent boys and girls [48][49][50][51][52][53].…”
Section: Exercise Performed On the Day Preceding A High-fat Mealmentioning
confidence: 84%
See 4 more Smart Citations
“…Since 2014, 36 studies have confirmed that exercise performed on the evening prior to a morning high-fat meal (that is, a meal containing above 0.7 g of fat per kg body mass) lowers PPL, compared to no exercise. This has been shown in young, middle-aged and/or older men [14,21,[33][34][35][36][37][38][39][40][41][42]22,43,76,77,23,[27][28][29][30][31][32], young men and women [44], young or middle-aged women [45,67], normal and overweight individuals [68], overweight and obese individuals [24,46,47] and adolescent boys and girls [48][49][50][51][52][53].…”
Section: Exercise Performed On the Day Preceding A High-fat Mealmentioning
confidence: 84%
“…TAG reduction of 22% (range 4 to 35%) [14,28,[37][38][39][40][41][42][43][44][45][46]29,[47][48][49][50][51][52][53][54][55][56]30,[57][58][59][60][61][62][63][64][65][66]31,67,68,[32][33][34][35][36]. iv.…”
Section: Accepted Manuscriptunclassified
See 3 more Smart Citations